مسؤولية مراجعي الحسابات في اكتشاف الأخطاء والغش في القوائم المالية (دراسة ميدانية لعينة من مراجعي الحسابات في الجزائر) - حولي, محمد (جامعة الوادي - University of Eloued, 2017)
هدفت هذه الدراسة إلى التعرف على مدى مسؤولية مراجعي الحسابات في اكتشاف الأخطاء وأعمال الغش في القوائم المالية للمؤسسات الجزائرية، ولتحقيق هذا الهدف تم بناء استبانة وزعت عشوائيا على عينة مجتمع الدراسة المتكون من مراجعي الحسابات، وعددهم ثمانون "80" مراجع، المسترد منها ثلاثة وخمسون "53" صالحة للتحليل الاحصائي أي ما نسبته 66.25% من عينة الدراسة. وتوصلت الدراسة إلى أنه هناك إدراك لدى مراجعي الحسابات في الجزائر حول مسؤولياتهم عن كشف الأخطاء وأعمال الغش، في حين أنهم غير ملزمون قانونا على اكتشاف الغش بل تقع على عاتق المكلفين بالرقابة والحوكمة (الإدارة)، إلا أنه على المراجع بدل العناية الممكنة بممارسة التشكيك المهني، وذلك في عملية التخطيط وإجراءات المراجعة لإبداء رأي سليم وواضح ذو مصداقية وأكثر شفافية. This study aimed to identify the extent of the responsibility of the Auditors in the detection of errors and fraud in the financial statements of the Algerian Institutions. To achieve this goal, a questionnaire has been designed and was randomly distributed on The study sample community, which consists of 80 auditors. Only 53 questionnaires were valid for the statistical analysis, representing 66.25% of the study sample that have been collected.The study concluded that the auditors in Algeria are aware of their responsibilities towards the detection of errors and fraud. However, they are not legally obliged to detect fraud, because it is the concern of those who are in charge of control and governance (Management). In addition, the auditor should make extra effort to exercise professional skepticism, in the planning process and audit procedures to provide a sound, clear, credible and more transparent opinion.
The responsibility of the auditors in detecting errors and fraud in the financial statements (Field study of a sample of auditors in Algeria)
مقال
Keywords: مراجعي الحسابات، مسؤولية، الغش، الأخطاء....